The Effect of Modern Technology in Employing Alternative Materials in Interior Architecture Vocabulary - Dr/ Ahmed Fathy elsayed (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2024)
The environmental engineering goal is to ensure the internal human space safety. Although the huge technological and industrial development in the late sixties had an adverse effect, which led to a pollution increasing and a global energy crisis, also it changed interior design ideas without considering materials standards and their impact on internal human environment. Later, a stage of reconsideration of the negative effects occurred to correct the path. That awakening was reflected on architecture to bring new ideas such as ecological, green and sustainable architecture. Sustainable design concept doesn’t mean planning only a natural interior space, as a major part of it depends on calculating the electrical energy consumed and the polluting gases it produces until the design becomes complete. There is no doubt that design trinity, material and economy embodies mutual complicated relationships. from here the problem of neglecting and discouraging the use of alternative materials from nature or recycled in interior design works arose, although it can help in finding a modern treatment for different interior design works, also to reduce pollutants in the internal space. Therefore, scientific studies must lead the way to develop new techniques and ideas to process traditional materials that are currently available, as well as researching nature to provide more environmental materials while at the same time responding to the requirements of the occupants of various activities spaces.